2017
DOI: 10.13075/ijomeh.1896.00943
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and mental health among teachers in relation to psychosocial job characteristics and burnout

Abstract: Objectives: The objective of the study has been to assess the associations between psychological distress and exposure to workplace bullying, taking into account possible influence of adverse psychosocial job characteristics and occupational burnout in a sample of Kaunas (Lithuania) teachers. Material and Methods: The study sample included 517 teachers from 13 secondary schools and was conducted in 2014. The participants filled in the anonymous questionnaire (response rate 71.3%). Twenty-two-item Negative Acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 26 publications
4
52
1
12
Order By: Relevance
“…Moreover, in support of the cognitive model of abusive supervision by Chan and McAllister (1) the perception of bullying is associated with paranoid thinking in both UK and French teachers, meaning that the more teachers perceive workplace bullying, the more they report paranoia and vice-versa. However an in contrast to what was found by Bernotaite and Malinauskiene (14) in their sample of Lithuanian teachers (14), workplace bullying was not statistically significantly associated with negative affect in the sample of French teachers and this may be explained by the fact that the bullying that French teachers experienced was perceived to be rare.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, in support of the cognitive model of abusive supervision by Chan and McAllister (1) the perception of bullying is associated with paranoid thinking in both UK and French teachers, meaning that the more teachers perceive workplace bullying, the more they report paranoia and vice-versa. However an in contrast to what was found by Bernotaite and Malinauskiene (14) in their sample of Lithuanian teachers (14), workplace bullying was not statistically significantly associated with negative affect in the sample of French teachers and this may be explained by the fact that the bullying that French teachers experienced was perceived to be rare.…”
Section: Discussioncontrasting
confidence: 99%
“…This study will address those issues and will use a cognitive and behavioral framework of cognitions, affect, and behavior (1,2) and apply it to the workplace by developing a model and applying it to cross-cultural samples of French and UK teachers (see Figure 1) and making as well comparisons between the two. This constitutes an advancement to the current literature, because research that was done previously can be considered to be rather a-theoretical and lacking a clear theoretical explanation for the relationships that are observed between workplace bullying and deviance and the poor mental health of teachers (12,14). Research in this area also uses self-report instruments to measure concepts such as, workplace bullying (4), and those instruments measure perceptions and not actual observable behavior, hence a cognitive perspective should be used to inform relationships between concepts.…”
Section: Introductionmentioning
confidence: 99%
“…We found coworkers were the most common source of bullying. Workplace bullying has been reported in many occupations, including nurses and teachers and researchers have shown that managers or supervisors and coworkers are typically identified as the perpetrator of bullying behavior . Specifically, our findings were similar to other studies which have reported a high level of coworker bullying among those in the education sector, rather than bullying from students and their parents .…”
Section: Discussionsupporting
confidence: 87%
“…Teachers who have been victims of nonphysical WPV on the job have higher levels of job strain, emotional exhaustion, and burnout, and these negative outcomes are exacerbated by low social support at work . Researchers have indicated teachers' job satisfaction decreased and burnout increased as experiences of nonphysical WPV increased .…”
Section: Discussionmentioning
confidence: 99%
“…Mean, cruel, and/or disrespectful behaviors are-by definition-relational: One person or group is acting in particular hurtful ways to another. In addition to students bullying other students, it has been found that teachers bully students, students bully teachers (Twemlow et al 2006;Pervin and Turner 1998), and teachers can suffer in bullying climates as much as students do (Bernotaite and Malinauskiene 2017). Again, there are virtually always witnesses who see or hear about these behaviors (Atlas and Pepler 1998;Craig and Pepler 1997;Craig et al 2000;Smokowski and Evans 2019).…”
mentioning
confidence: 99%